Regional Trade in Food Staples : Prospects for Stimulating Agricultural Growth and Moderation Food Security Crises in Eastern and Southern Africa - World Bank (Washington, DC, 2012)
This report focuses on growing trade in food staples in the Southern and Eastern African region of Africa as one of the largest growth opportunities available to African farmers. This paper examines the impact of regional trade in food staples, both for maintaining farmer incentives in surplus food production zones and for moderating price spikes in deficit areas. The paper begins by identifying the geographic extent of major maize market sheds in Eastern and Southern Africa. It then focuses on the South Eastern Africa market shed, the one centered in Malawi, Northern Mozambique and Zambia. This analysis concentrates on the regions two most important food staples, maize and cassava. Given the volatility of the region's rainfed maize production, this section aims to empirically evaluate the impact of maize production shocks on staple food prices, production incentives, consumption and trade. To do so, the paper develops a spatially disaggregated model o f maize and cassava markets in order to evaluate the impact of supply shocks, with and without cross-border trade.